Experimental and Theoretical Investigations of Hard Rocks at High Temperature: Applications in Civil Engineering - Mambou Ngueyep Luc Leroy; Foguieng Wembe Marius; Ngapgue François (Advances in Civil Engineering)
This review paper aims to survey and discuss recent theoretical and experimental works reporting the temperature effects on the mechanical properties of rocks like granite, gabbro, gneiss, marble, sandstone, basalt, limestone, and argillite to permit the new challenge in this domain. The effect of high temperatures on various mechanical and physical material properties (Young’s modulus, porosity, tensile and compressive strengths, P-wave velocity, permeability, thermal damage, and expansion) is analyzed. This work shows that hard rock mechanical and physical properties evolutions are strongly related to the evolution of the microstructure caused by the geological history, cracks nucleation occurrences, recrystallization, dehydroxylation, and dehydration reactions. However, it should be emphasized that these studies were not conducted on all types of intrusions and all rocks types. Meanwhile, it has been noticed that variations in temperature could lead to contradictory phenomena. Therefore, different trends were observed for the evolution of physical properties of rocks. There is an increase in porosity approximately 80% above 500°C. In general, for volcanic’s rock, the loss mass and thermal conductivity were drastically observed at low temperatures around 200°C with an antinomic phenomenon. Sandstone, granite, and argillite present the model whose behaviors with thermal load are too much explored accordingly with experiments compared with other rocks. Argillite at 200°C and sandstone and granite at 400°C undergo seriously damage. There is 100°C gap between the results obtained in real-time and those obtained after cooling. Moreover, 300°C can be considered as the critical temperature for real-time temperature heat treatment at which rocks lose almost about 80% of their performance. Otherwise, it is not easy to predict the behavior at high temperature of volcanic rocks like basalt and metamorphic rocks like gneiss which present the complexity in their behavior. For plutonic and metamorphic rocks, 600°C is the critical thermal load. At this temperature, the modulus of elasticity as well as the compressive strength of the most explored rock shows a significant decrease of about 75% for hard rocks. In sum, high temperature damages significantly the mechanical performance of rock. It is the reason for which these results may be useful to characterize the damage and thus predict the dramatic consequences of large temperature fluctuations on engineering structures in the rock.